2019
DOI: 10.1111/jopr.13009
|View full text |Cite
|
Sign up to set email alerts
|

The Friction Clasp

Abstract: This clinical report describes a modification of the conventional direct retainer design, which incorporates advantages of the dual path partial denture, but with a greater ease of design and fabrication. The main advantage of this technique is minimizing the clasp display on Class III and Class IV removable partial denture prostheses. A clinical example using this design is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…King et al suggested the use of lingual retentive clasps, and Highton et al proposed the use of palatal I bars or dual paths or rotational paths of insertion [ 8 , 9 ]. Others have attempted to camouflage the visible clasps by covering them with tooth-colored veneers [ 9 , 10 , 11 , 12 , 13 ], while removable partial dentures with precision attachments are aesthetically satisfying, but they are expensive and more technique-sensitive [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…King et al suggested the use of lingual retentive clasps, and Highton et al proposed the use of palatal I bars or dual paths or rotational paths of insertion [ 8 , 9 ]. Others have attempted to camouflage the visible clasps by covering them with tooth-colored veneers [ 9 , 10 , 11 , 12 , 13 ], while removable partial dentures with precision attachments are aesthetically satisfying, but they are expensive and more technique-sensitive [ 14 ].…”
Section: Introductionmentioning
confidence: 99%